A legal guide to urban and sustainable development for planners, developers and architects - 207218 Slone, Daniel K. (Daniel Kennon); Goldstein, Doris S. (Doris Sussman); Gowder, W. Andrew (Hoboken, NJ : Wiley, 2008)
Includes bibliographical references (p. 338-345) and index